The Management of Acute Anterior Uveitis Complicating Spondyloarthritis: Present and Future. (14th October 2018) - Biggioggero, Martina; Crotti, Chiara; Becciolini, Andrea; Miserocchi, Elisabetta; Favalli, Ennio Giulio
Abstract : Spondyloarthropathies (SpA) encompass a group of chronic inflammatory diseases sharing common genetic and clinical features, including the association with HLA-B27 antigen, the involvement of both the axial and the peripheral skeleton, the presence of dactylitis, enthesitis, and typical extra-articular manifestations such as psoriasis, inflammatory bowel disease, and acute anterior uveitis (AAU). The latter is commonly reported as a noninfectious acute inflammation of the anterior uveal tract and its adjacent structures. AAU may affect more than 20% of SpA patients representing the most common extra-articular manifestation of the disease. Considering the potential consequences of untreated AAU, early diagnosis and aggressive treatment are crucial to avoid complications of remittent or chronic eye inflammation, such as visual loss and blindness. The management of SpA has dramatically improved over the last decades due to the development of new treat-to-target strategies and to the introduction of biologic disease modifying antirheumatic drugs (bDMARDs), particularly tumor necrosis factor alpha inhibitors (TNFis), currently used for the treatment of nonresponder patients to conventional synthetic agents. Along with the improvement of musculoskeletal features of SpA, bDMARDs provided an additional effect also in the management of AAU in those patients who are failures to topical and systemic conventional therapies. Nowadays, five TNFis, one interleukin-17, and one interleukin 12/23 blocker are licensed for the treatment of SpA, with different proven efficacy in preventing and treating ocular involvement. The aim of this review is to summarize the current options and to analyze the future perspectives for the management of SpA-associated AAU.